MAKNA PENGGUNAAN SIMBOL UKIRAN “PA’MANUK LONDONG” PADA MASYARAKAT TORAJA - deprianus sarlis (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2016)
Abstract The problem in this research are the meaning of symbols Carving is Pa 'Manuk Londong in Toraja Society and How to Use of Symbols Carving Pa' Manuk Londong in Toraja people. The purpose of this research were to determine the meaning of the symbols carved Pa 'Manuk Londong and use symbols carved Pa' Manuk Londong the Toraja people. The location of this research was held in Lamunde village, District Tinondo, East Kolaka. The used theory is the symbol theory by Susanne Langer. In this research the number of informants as many as 5 people to represent the Toraja society. Data used in this research is qualitative data and data analysis techniques used in this research is qualitative interpretative analysis. The results of this research indicate that the symbol Carving Pa 'Manuk Londong used Torajanese the Toraja traditional house (Tongkonan and reeds) and duplicate Toraja traditional house that is in use by the Toraja people both in Tanah Toraja (Toraja Regency and North Toraja) and the there is the migration areas that have significance both in terms of its use, color engravings and drawings roosters used. This research is expected to provide benefits and contributions of Sciences for the community, especially for Toraja people in overseas. This research is also expected to served the benefit in the development of Communication Studies, especially on research Meaning Use of Symbols Carving "Pa 'Manuk Londong" In the Toraja people. Keywords: Symbol Of Communication, Meaning Use Of Carving "Pa'manuk Londong", Toraja Society.